Epileptic seizures induced by pentylenetetrazole kindling accelerate Alzheimer-like neuropathology in 5×FAD mice - Zou, Yulian; Wang, Chengyan; Li, Huang; Zhong, Meihua; Lin, Jin; Hu, Yan; Chen, Zhou; Gan, Chen-Ling (Frontiers in Pharmacology, 2024)
Clinical studies have shown that epileptic seizures worsen Alzheimer's disease (AD) pathology and related cognitive deficits; however, the underlying mechanism is unclear. To assess the effects of seizures on the progression of AD, chronic temporal lobe epilepsy was induced in five familial AD mutation (5×FAD) mice by kindling with the chemoconvulsant pentylenetetrazole (PTZ) at 3-3.5 months of age. The amyloidogenic pathway, tauopathy, synaptic damage, neuronal death, neurological inflammatory response and associated kinase signaling pathway dysregulation were examined at 9 months of age. We found that APP, p-APP, BACE1, Aβ and kinase-associated p-tau levels were elevated after PTZ kindling in 5×FAD mice. In addition, PTZ kindling exacerbated hippocampal synaptic damage and neuronal cell death, as determined by scanning electron microscopy and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) staining, respectively. Finally, the levels of the neuroinflammation markers GFAP and Iba1, as well as the inflammatory cytokine IL-1β, were increased after PTZ insult. PTZ kindling profoundly exacerbated extracellular regulated kinase (ERK)-death-associated protein kinase (DAPK) signaling pathway overactivation, and acute ERK inhibitor treatment downregulated Aβ production and p-APP and p-tau levels in epileptic 5×FAD mice. In addition, long-term use of the antiseizure drug carbamazepine (CBZ) alleviated seizure-induced accelerated amyloid and tau pathology and ERK-DAPK overactivation in 5×FAD mice. Collectively, these results demonstrate that seizure-induced increases in AD-like neuropathology in 3 5×FAD mice are partially regulated by the ERK-DAPK pathway, suggesting that the ERK-DAPK axis could be a new therapeutic target for the treatment of AD patients with comorbid seizures.